Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1124/jpet.110.165563
|View full text |Cite
|
Sign up to set email alerts
|

Altered Protein Kinase C Regulation of Pulmonary Endothelial Store- and Receptor-Operated Ca2+Entry after Chronic Hypoxia

Abstract: Chronic hypoxia (CH)-induced pulmonary hypertension is associated with decreased basal pulmonary artery endothelial cell (EC) Ca 2ϩ , which correlates with reduced storeoperated Ca 2ϩ (SOC) entry. Protein kinase C (PKC) attenuates SOC entry in ECs. Therefore, we hypothesized that PKC has a greater inhibitory effect on EC SOC and receptoroperated Ca 2ϩ entry after CH. To test this hypothesis, we assessed SOC in the presence or absence of the nonselec-in freshly isolated, Fura-2-loaded ECs obtained from intrapul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The effect of PKC on ASIC1 has been shown to be either stimulatory or inhibitory, depending on the PKC isoform and phosphorylation site (3,4,16,50). Consistent with previous data from our laboratory in isolated pulmonary arteries and pulmonary arterial endothelial sheets (32,39), activation of PKC suppressed SOCE in PASMC. These data are in line with reports that PKC activation reduces current amplitude of human ASIC1 in glioma cells and Xenopus oocytes (3,4).…”
Section: Discussionsupporting
confidence: 81%
“…The effect of PKC on ASIC1 has been shown to be either stimulatory or inhibitory, depending on the PKC isoform and phosphorylation site (3,4,16,50). Consistent with previous data from our laboratory in isolated pulmonary arteries and pulmonary arterial endothelial sheets (32,39), activation of PKC suppressed SOCE in PASMC. These data are in line with reports that PKC activation reduces current amplitude of human ASIC1 in glioma cells and Xenopus oocytes (3,4).…”
Section: Discussionsupporting
confidence: 81%
“…Ca(v)3.1 has been specifically linked to the expression and activation of cyclin D further supporting its importance in regulating cell cycle suppressing [14]. In pulmonary artery endothelial cells (PAEC), isolated from the CH induced experimental model of PH, a decreased ATP-dependent and depolarization induced Ca 2+ entry via mibefradil-sensitive T-type channels has been observed [15]. Such function regulation would imply a potential role in PH and in particular in pulmonary vascular remodeling.…”
Section: Voltage-dependent Calcium Channelsmentioning
confidence: 99%
“…Recent data have demonstrated that PKC-␣ mediates ACh-induced activation of TRPV4-dependent Ca 2ϩ influx in vascular ECs (1). On the other hand, chronic hypoxia enhances PKC-dependent inhibition of Ca 2ϩ entry in ECs of rat intrapulmonary arteries (56). The role of enhanced PKC activity in impaired EC Ca 2ϩ signaling in uteroplacental arteries of diabetic pregnant rats requires further investigation.…”
Section: H942mentioning
confidence: 99%